The Show Must Go On! Exploring Students’ Self-confidence Position by Using Theater in the EFL Class (2023)
ABSTRACT : This action research aimed at promoting students’ self-confidence by exploring their identities while using theater workshops. It was conducted in a public rural school in Rionegro, Antioquia with 34 students in tenth grade. Action strategies included exploration of identity through theater workshops. Data collection instruments were the teacher’s and student’s journal, student’s questionnaires and focus groups. Findings referred to 13 participant cases presented as: Theater a Double-edged Sword to Move Identity Position between Self-confidence and Lack of Confidence, Self-confidence Development Disrupted by Classroom Environment Dynamics and Identity Positioning regarding the Language, and Students’ Divergent Perceptions for Learning English with Theater.